Booster Vaccination With GVGH Shigella sonnei 1790GAHB GMMA Vaccine Compared to Single Vaccination in Unvaccinated Healthy European Adults: Results From a Phase 1 Clinical Trial - Launay, Odile; Ndiaye, Augustin G. W.; Conti, Valentino; Loulergue, Pierre; Sciré, Antonella Silvia; Landre, Anais Maugard; Ferruzzi, Pietro; Nedjaai, Naouel; Schütte, Lena Dorothee; Auerbach, Joachim; Marchetti, Elisa; Saul, Allan; et al. (Frontiers in Immunology, 2019)
The investigational Shigella sonnei vaccine (1790GAHB) based on GMMA (generalized modules for membrane antigens) is immunogenic, with an acceptable safety profile in adults. However, pre-vaccination anti-S. sonnei lipopolysaccharide (LPS) antibody levels seemed to impact vaccine-related immune responses. This phase 1, open-label, non-randomized extension study (ClinicalTrials.gov: NCT03089879) evaluated immunogenicity of a 1790GAHB booster dose in seven adults with undetectable antibodies prior to priming with three 1790GAHB vaccinations 2–3 years earlier (boosted group), compared to one dose in 28 vaccine-naïve individuals (vaccine-naïve group). Anti-S. sonnei LPS serum IgG geometric mean concentrations and seroresponse (increase of ≥25 EU or ≥50% from baseline antibody ≤50 EU and ≥50 EU, respectively) rates were calculated at vaccination (day [D]1), D8, D15, D29, D85. Safety was assessed. Geometric mean concentrations at D8 were 168 EU (boosted group) and 32 EU (vaccine-naïve group). Response peaked at D15 (883 EU) and D29 (100 EU) for the boosted and vaccine-naïve groups. Seroresponse rates at D8 were 86% (boosted group) and 24% (vaccine-naïve group) and increased at subsequent time points. Across both groups, pain (local) and fatigue (systemic) were the most frequent solicited adverse events (AEs). Unsolicited AEs were reported by 57% of boosted and 25% of vaccine-naïve participants. No deaths, serious AEs, or AEs of special interest (except one mild neutropenia case, possibly vaccination-related) were reported. One 1790GAHB dose induced a significant booster response in previously-primed adults, regardless of priming dose, and strong immune response in vaccine-naïve individuals. Vaccination was well tolerated.